1990
DOI: 10.1128/jb.172.1.260-265.1990
|View full text |Cite
|
Sign up to set email alerts
|

Lignin peroxidase-negative mutant of the white-rot basidiomycete Phanerochaete chrysosporium

Abstract: Phanerochaete chrysosporium produces two classes of extracellular heme proteins, designated lignin peroxidases and manganese peroxidases, that play a key role in lignin degradation. In this study we isolated and characterized a lignin peroxidase-negative mutant (lip mutant) that showed 16% of the ligninolytic activity (14C-labeled synthetic lignin -* '4CO2) exhibited by the wild type. The lip mutant did not produce detectable levels of lignin peroxidase, whereas the wild type, under identical conditions, produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 45 publications
3
25
1
1
Order By: Relevance
“…At high intracellular cAMP concentrations, both LIPs and MNPs are produced; at intermediate cAMP concentrations, only MNPs are produced; and at low concentrations, neither LIPs nor MNPs are produced. These results on differential regulation of LIP and MNP production by cAMP are consistent with our earlier results (21), which showed that an apparent regulatory mutant of P. chrysosporium, designated lip mutant, lacks the ability to produce the LIP isozymes but produces a normal complement of MNP isozymes, indicating that LIP production and MNP production are regulated differently. Similar differential regulation of LIPs and MNPs by manganese concentration in the growth medium has been observed (22,23) and the manganese requirement for transcription of the MNP gene has also been reported (24,25).…”
Section: Discussionsupporting
confidence: 92%
“…At high intracellular cAMP concentrations, both LIPs and MNPs are produced; at intermediate cAMP concentrations, only MNPs are produced; and at low concentrations, neither LIPs nor MNPs are produced. These results on differential regulation of LIP and MNP production by cAMP are consistent with our earlier results (21), which showed that an apparent regulatory mutant of P. chrysosporium, designated lip mutant, lacks the ability to produce the LIP isozymes but produces a normal complement of MNP isozymes, indicating that LIP production and MNP production are regulated differently. Similar differential regulation of LIPs and MNPs by manganese concentration in the growth medium has been observed (22,23) and the manganese requirement for transcription of the MNP gene has also been reported (24,25).…”
Section: Discussionsupporting
confidence: 92%
“…Under ligninolytic conditions, P. chrysosponum secretes two heme peroxidases (LiP and MnP) in addition to an H202-generating system (18,32). These two peroxidases appear to be primarily responsible for the oxidative depolymerization of this heterogeneous, random phenylpropanoid polymer (4,18,23,27,32,54). Other studies have demonstrated that P. chrysosponium is capable of mineralizing many persistent environmental pollutants (5,6,10,21,28,35,49), including, to a limited extent, TCDD (6).…”
mentioning
confidence: 99%
“…Screening for potential fungi using chromogenic substances 0.1% Guaiacol, 0.1% azureB, and 0.0025% phenol red were used for the screening of potential fungi that could produce peroxidase and laccase enzymes [30][31][32][33] . Three 7-mm agar plugs containing fungal mycelia from 7-day-old cultures on MEA plates were placed on an MM plate that contained each chromogenic substance.…”
Section: Fungal Isolationmentioning
confidence: 99%
“…However, eight isolates (14.5%) were able to change at least one of the three chromogenic substances. Among the latter, three isolates consisting of F18, S5, and T20 gave the widest zone of colour changes and, therefore, were selected for further characterization because the colour changes of these substances have been reported to be related to the production of peroxidase and laccase enzymes, which are responsible for the degradation of PAHs [30][31][32][33] .…”
Section: Fungal Isolation and Screeningmentioning
confidence: 99%